Analyzing the Financial Resilience of Islamic Banks in Indonesia Amid the COVID-19 Pandemic: A Comparative Study of Stock Price Dynamics - Zulbetti*, Rita; Muzaffirah, Adzirah (Program Studi Keuangan & Perbankan, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2023)
This research aims to analyze the impact of the Covid-19 pandemic on the stock prices of Shariah-compliant banks in Indonesia and test the significance of price differences during the 350 days before and after the Covid-19 outbreak in Indonesia. Stock price data was obtained from the Indonesia Stock Exchange and Yahoo Finance, with the research sample including Bank Syariah Indonesia, BTPN Syariah, and Bank Panin Dubai Syariah. The results indicate that the stock prices of Shariah-compliant banks remained relatively stable during the Covid-19 pandemic and even experienced significant increases after the outbreak. There are significant differences in stock prices before and after Covid-19, as well as differences between the average stock prices of BRIS, BTPS, and PNBS. In conclusion, Shariah-compliant banks listed on the Indonesia Stock Exchange demonstrated resilience and positive growth during the pandemic, with significant differences in stock prices before and after the Covid-19 outbreak. Keywords: Stock Prices; Islamic Banks; Paired Sample T-Test; One Way ANOVA; Post Hoc Test Abstrak Penelitian ini bertujuan untuk menganalisis dampak pandemi Covid-19 terhadap harga saham Bank Syariah di Indonesia dan menguji signifikansi perbedaan harga saham selama 350 hari sebelum dan setelah wabah Covid-19 memasuki Indonesia. Data harga saham diambil dari Bursa Efek Indonesia dan Yahoo Finance, dengan sampel penelitian meliputi Bank Syariah Indonesia, BTPN Syariah, dan Bank Panin Dubai Syariah. Hasil penelitian menunjukkan bahwa harga saham Bank Syariah cenderung stabil selama pandemi Covid-19, bahkan mengalami kenaikan setelah wabah. Terdapat perbedaan signifikan dalam harga saham sebelum dan setelah Covid-19, serta perbedaan antara rata-rata harga saham BRIS, BTPS, dan PNBS. Kesimpulannya, Bank-bank Syariah di Bursa Efek Indonesia menunjukkan ketahanan dan pertumbuhan positif selama pandemi, dengan perbedaan yang signifikan dalam harga saham sebelum dan setelah pandemi Covid-19. Kata Kunci: Harga Saham; Bank Syariah; Uji-T Sampel Berpasangan; One-Way ANOVA ; Post Hoc Test